Disparity in liver cancer incidence and chronic liver disease mortality by nativity in Hispanics: The Multiethnic Cohort. Issue 9 (24th February 2016) - Setiawan, Veronica Wendy; Wei, Pengxiao C.; Hernandez, Brenda Y.; Lu, Shelly C.; Monroe, Kristine R.; Le Marchand, Loic; Yuan, Jian Min
Abstract : BACKGROUND: Hepatocellular carcinoma (HCC) and chronic liver disease (CLD) are major causes of morbidity and mortality among Hispanics. Disparities in the incidence of HCC and in CLD deaths by nativity in Hispanics have been reported. Whether individual‐level risk factors could explain these disparities was assessed in a prospective study of 36, 864 Hispanics (18, 485 US‐born and 18, 379 foreign‐born) in the Multiethnic Cohort. METHODS: Risk factors were assessed with a baseline questionnaire and Medicare claim files. During a 19.6‐year follow‐up, 189 incident cases of HCC and 298 CLD deaths were identified. RESULTS: The HCC incidence rate was almost twice as high for US‐born Hispanic men versus foreign‐born Hispanic men (44.7 vs 23.1), but the rates were comparable for women (14.5 vs 13.4). The CLD mortality rate was about twice as high for US‐born Hispanics versus foreign‐born Hispanics (66.3 vs 35.1 for men and 42.2 vs 19.7 for women). Heavy alcohol consumption was associated with HCC and CLD in foreign‐born individuals, whereas the current smoking status, hepatitis B/C viral infection, and diabetes were associated with both HCC and CLD. After adjustments for these risk factors, the hazard rate ratios for HCC and CLD death were 1.58 (95% confidence interval, 1.00‐2.51) and 1.85 (95% confidence interval, 1.25‐2.73), respectively, for US‐born Hispanics versus foreign‐born Hispanics. CONCLUSIONS: US‐born Hispanics, particularly males, are at greater risk for HCC and death from CLD than foreign‐born Hispanics. Overall known differences in risk factors do not account for these disparities. Future studies are warranted to identify factors that contribute to the elevated risk of HCC development and CLD death in US‐born Hispanics. Cancer 2016;122:1444–1452 . © 2016 American Cancer Society . Abstract : US‐born Hispanics, particularly males, are at greater risk for liver cancer and death from chronic liver disease than foreign‐born Hispanics. Overall known differences in risk factors do not account for these disparities.